Modification and Engineering of Portable Fish Aggregating Devices (Fads) With The Addition of Acoustic Sensors - Mulia, Citra; Setiawan, Ari; Hidayatullah, Rizqy; Prayoga, Arif (Politeknik Negeri Bengkalis, 2024)
The portable rumpon is a movable fish aggregating device that consists of a float and attractor, without anywood or permanent structures on it. This portable rumpon is commonly used in waters with moderate currents. It isusually equipped with sonar to determine the abundance of fish congregating in the area. Modifications to the shapeof the portable rumpon and the engineering addition of acoustic sensors are expected to increase the catch of fish,allowing them to gather around it. The acoustic sensors used have a frequency range of 10,000-15,000 Hz, which is asound wave favored by fish. The generated sound waves are anticipated to enhance the catch results, as indicated bythe number of fish that gather around the rumpon. The operation of the portable rumpon can be conducted alongsidefishing gear to achieve optimal results.